Rental yield as alternative to interest rate in pricing musyarakah mutanaqisah home financing - the case for Malaysia. - Redzuan, Nur Harena; Kassim, Salina; Abdullah, Adam (IIUM Press, 2018)
The current practice of the Islamic banks in Malaysia is relying on the market interest rate as the reference benchmark pricing for musyarakah mutanaqisah home financing. It has been a subject of intense debate among scholars, researchers, industry players, and policymakers. While it is not prohibited, Muslim scholars have highly discouraged this practice as it could lead to a possible convergence between the practices of the Islamic banks and the conventional counterparts. Therefore, this study proposes rental yield an alternative reference benchmark pricing mechanism for musyarakah mutanaqisah home financing. The aim of the study is to assess whether rental yield is reflective of the real economic conditions. In achieving its objective, the study tests the relationships between rental yield with the macroeconomic and housing market variables. The study focuses on Malaysia and uses annually data frequency covering the period from 1988 to 2015 using Autoregressive Distributed Lag (ARDL)cointegration test. The study provides evidence that the proposed rental yield has long-run and short-run relationships with macroeconomic and housing market variables. The analysis shows that a short period required for the model to converge to the long-run equilibrium. The findings of this study would provide important insights on the viability of rental yield as an alternative to interest rate in pricing musyarakah mutanaqisah home financing.